Present concepts of non-traditional methods of growing of metal whisker crystals. Pulling of whiskers from solution - Артемьев, Сергей Робленович (Technology audit and production reserves, 2015)
The material of articles were reviewed and analyzed the results of previous studies of whisker crystals on non-traditional growing methods, namely, one of them – the "pull" of metal whiskers from solutions. Analysis of published data shows that the problem in modern conditions given enough attention to that, no doubt, talking about the relevance of the research topic and, therefore, these issues need to be addressed. The results of this analysis show that if prepared solution at a certain temperature is rapidly cooled to a lower temperature, there appear corresponding metal whiskers. The whiskers begin to appear again after the completion of the main stage of crystallization and if it begins to lower the temperature, the amount of the crystal needles will gradually increase. Reaching a certain "threshold overflow" volume growth of whisker crystals becomes an avalanche, and then almost stopped, at the final stage it is appeared whisker curled in a spiral around the axis of growth. The growth of whiskers of metal salts by rapid cooling of saturated solutions occurs at dislocations occurring on the particles of impurities. It is only stopped after the complete drying following solutions. The spectrum of use of whisker crystals in modern industry is expanded, so keeping and use of research will improve the implementation of environmental requirements for the protection of human health and environment.